Development of a Mobile Robot: Robotic Guide Dog for Aid of Visual Disabilities in Urban Environments - Bruno, Diego; Assis, Marcelo; Osório, Fernando (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
The general objective of this work is to develop a mobile robotic platform that is able to avoid obstacles for the benefit of visually impaired people. The idea is that this platform is a robot "guide dog" ~for visually impaired persons, and animal guide dogs like these have very high costs (on average 40 thousand dollars - Our current robotic prototype has a cost of 400 dollars), also need a long time for training (more than 1 year), being therefore inaccessible to many visually impaired persons. Our work then turns to social robotics, where we have a big problem with disabled people and who do not get freedom to move around in urban spaces without the help of a caregiver. By collecting data from ultrasound sensors, managing a possible path to the target point in an autonomous manner, using a computer vision system to recognize and treat the obstacles encountered, representing these in the form of audio to the user. The prototype was developed to serve as a platform for research in the development of navigational algorithms and computer vision systems of the automation laboratory of the (omitted for blind review). The robot presented good results in tests with navigation algorithms and computer vision that were applied to validate this platform in tests with visually impaired people in IDVC - (Catanduva Institute for the Visually Impaired).